Analyzing Effective Way Of Keeping Existing Customer In Service Oriented Organization With CRM By Using Data Mining Techniques - Seyed Danesh, Mir Mohammad (2011)
This research is aimed to specify the characteristics resulting in attrition of customer, as the most valuable property of an organization, and in this path attempts have been carried out to identify these characteristics by selecting a reliable model using past experiences and research, and finally to test this model. employing real data, in one of Iranian mobile communications operators.